Pengaruh Inflasi, Kurs, dan Investasi Infrastruktur terhadap Pertumbuhan Ekonomi di Indonesia: Analisis Menggunakan Model VECM (1993-2023) - Putra, Trischa; Rahayuningsih, Eni Sri (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
This study examines the relationship between inflation, exchange rates, and infrastructure investment on economic growth in Indonesia using the Vector Error Correction Model (VECM) approach for the period 1993–2023. Secondary data were obtained from official institutions such as Bank Indonesia, the Central Bureau of Statistics, and the Ministry of Public Works. The analysis reveals that inflation has a significant negative impact on economic growth in the long term, while exchange rates and infrastructure investment show no significant influence. The VECM model also identifies a significant error correction mechanism, with a negative error correction coefficient of 41.49% for the economic growth variable. Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) analyses indicate minimal contributions of exchange rates and infrastructure investment to the variability of economic growth. This study recommends controlling inflation through monetary policy, stabilizing exchange rates, and enhancing infrastructure investment as strategies to foster sustainable economic growth in Indonesia.